PENINGKATAN KUALITAS PEMBERDAYAAN KELOMPOK TANI HUTAN DALAM PENGELOLAAN HASIL HUTAN BUKAN KAYU - Hendro Asmoro; Sumardjo Sumardjo; Djoko Susanto; Prabowo Tjitropranoto (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2021)
Non-timber forest products (NTFPs) management by the forest farmers group (FFG) is not optimal. This condition is thought to be related to the low quality of empowerment of FFG. This can be influenced by the effectiveness of group leadership, extension support, and support for external environmental factors as well as group internal environmental factors. The purposes of the study were: 1) to analyze the factors that influence the quality of FFG empowerment in the management of NTFPs and 2) to formulate model for improving the quality of FFG empowerment in the management of NTFP. The study was conducted in Desember 2016 - April 2017 in East Lampung District, Lampung Province and Sleman District, DI Yogyakarta Province. Respondents were 248 members of FFG who manage NTFPs based on census. The data were analyzed by using descriptive technique and Structural Equations Model. Result of the study showed that the factors that influence the quality of empowerment are extension support as well as FFG internal environment support.Efforts to improve the quality of empowerment can be carried out with:1) a model of enhancement of extension support that empowers FFG towards filtering power, competitiveness, and partnership power and 2) a model of increasing support for conducive internal environmental factors.